PEMBERDAYAAN DAN KEADILAN PROSEDURAL GURU: ANALISIS KUANTITATIF: PEMBERDAYAAN DAN KEADILAN PROSEDURAL GURU: ANALISIS KUANTITATIF - Heldy Ramadhan Putra (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
The objective of this research is to examine the effect of empowerment toward procedural justice of SDN regrouping teacher in South Jakarta. This research use quantitative approach with survey methods. The sample of this research is 200 Civil Servant teachers (PNS) of regrouping Elementary Public-School teachers which is appointed randomly from 59 Elementary Public-School in South Jakarta. Data collection was carried out by using instruments in form of questionnaires to measure four research variables. The result of this study indicate that empowerment has a direct positive effect toward procedural justice.